IMPLEMENTASI ALGORITMA K-MEANS UNTUK PENGELOMPOKAN DATA KEMISKINAN PROVINSI ACEH - Renita, Dayu; Khrisnawati, Erlin Ayu (Program Studi Teknologi Informasi, Fakultas Teknik, Universitas Udayana, 2024)
During the period September 2021-March 2022, percentage the poor population in Aceh Province fell from 15.53% to 14.64%. Even though it tends to decrease, this number must be managed so that the poverty rate in Aceh province decreases. The poverty rate in each district or city in Aceh province is influenced by different indicators. In this study using the K-Means algorithm method to determine classifying poverty levels in Aceh Province. Data was taken from 23 districts/cities with 3 variables, namely average school time (years), average per capita expenditure (thousands of rupiah) and number of poor people (thousands of people). The data was processed using RapidMiner Studio and obtained 4 clusters with each cluster namely cluster 0 consisting of 13 items, cluster 1 consisting of 4 items, cluster 2 consisting of 1 item, cluster 3 consisting of 5 items.